T3SS chaperone of the CesT family is required for secretion of the anti-sigma factor BtrA in Bordetella pertussis - Držmíšek, Jakub; Petráčková, Denisa; Dienstbier, Ana; Čurnová, Ivana; Večerek, Branislav (Emerging microbes & infections, 2023)
Bordetella pertussis is a Gram-negative, strictly human re-emerging respiratory pathogen and the causative agent of whooping cough. Similar to other Gram-negative pathogens, B. pertussis produces the type III secretion system, but its role in the pathogenesis of B. pertussis is enigmatic and yet to be elucidated. Here, we combined RNA-seq, LC-MS/MS, and co-immunoprecipitation techniques to identify and characterize the novel CesT family T3SS chaperone BP2265. We show that this chaperone specifically interacts with the secreted T3SS regulator BtrA and represents the first non-flagellar chaperone required for the secretion of an anti-sigma factor. In its absence, secretion but not production of BtrA and most T3SS substrates is severely impaired. It appears that the role of BtrA in regulating T3SS extends beyond its activity as an antagonist of the sigma factor BtrS. Predictions made by artificial intelligence system AlphaFold support the chaperone function of BP2265 towards BtrA and outline the structural basis for the interaction of BtrA with its target BtrS. We propose to rename BP2265 to BtcB for the Bordetella type III chaperone of BtrA.In addition, the absence of the BtcB chaperone results in increased expression of numerous flagellar genes and several virulence genes. While increased production of flagellar proteins and intimin BipA translated into increased biofilm formation by the mutant, enhanced production of virulence factors resulted in increased cytotoxicity towards human macrophages. We hypothesize that these phenotypic traits result indirectly from impaired secretion of BtrA and altered activity of the BtrA/BtrS regulatory node.
Keywords: Whooping Cough; Chromatography, Liquid; biofilm; Bacterial Proteins; tandemová hmotnostní spektrometrie; anti-sigma factor; regulace genové exprese u bakterií; chromatografie kapalinová; CesT chaperone; Bordetella pertussis; sigma faktor; Artificial Intelligence; lidé; Humans; T3SS; umělá inteligence; bakteriální proteiny; Sigma Factor; Tandem Mass Spectrometry; pertuse; Gene Expression Regulation, Bacterial